Pengaruh Kompetensi, Kompensasi dan Disiplin Kerja terhadap Motivasi Kerja dan Dampaknya pada Kinerja Pegawai Badan Keuangan Daerah Kabupaten Tanjung Jabung Timur - Pantun Bukit; Sudirman Sudirman; Tiska Mayzura (Universitas Batanghari, 2023)
This study aims to find out how the influence, Competence, Compensation and Work Discipline on Work Motivation and its impact on the Performance of Employees of the Regional Finance Agency of Tanjung Jabung Timur Regency. The research method uses quantitative methods using primary data and secondary data. The number of samples in this study was 61 people. Data management in this study used the SPSS 2022 Analysis tool. The analysis used in this study includes validity tests, reliability tests and Path Model Analysis. The results showed (1)description of the implementation of competence, compensation, work discipline, work motivation and performance in employees (2) Competence, compensation and work discipline have a simultaneous effect both directly and directly on the implementation of Compensation, indirect compensation for work motivation (3) Competence, compensation and work discipline have a partial and significant effect on work motivation (4) Competence, compensation and work discipline affect simultaneously both directly and significantly indirect to employee performance (5) Competence, compensation and work discipline have a partial and significant effect on employee performance, (6) Work motivation has a significant effect on employee performance in employees of the Tanjung Jabung Timur Regional Finance Agency. 9the effect of competence, compensation and work discipline on work motivation and its impact on the performance of employees of the Regional Finance Agency of Tanjung Jabung Timur Regency, Tanjung Jabung Timur Regional Finance Agency.